2009
DOI: 10.1038/jhh.2008.165
|View full text |Cite
|
Sign up to set email alerts
|

Assessing secular trends in blood pressure in children and adolescents

Abstract: Until recently, hypertension was rarely a matter of concern among children and adolescents. Perception of this condition has changed because of evidence showing that elevated blood pressure (BP) during childhood is not benign. Elevated BP in children is associated with left ventricular hypertrophy and a thickening of carotid intima-media thickness. 1 Furthermore, BP tracks over time and children with elevated BP are at high risk of developing hypertension in adulthood. 2 These findings support the potential fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Research demonstrates that the prevalence of hypertension has increased over the last decade as a result of the increase in overweight and obesity amongst children. 6 Monyeki et al, 10 who focused on a relatively small group of black children (n=203) from disadvantaged communities, reported a 3.9% prevalence of hypertension in 6 -7-year-old children. However, none of the 6 -7-year-old children fell into the overweight category, which could also possibly contribute to the lower prevalence of hypertension that was reported in the study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Research demonstrates that the prevalence of hypertension has increased over the last decade as a result of the increase in overweight and obesity amongst children. 6 Monyeki et al, 10 who focused on a relatively small group of black children (n=203) from disadvantaged communities, reported a 3.9% prevalence of hypertension in 6 -7-year-old children. However, none of the 6 -7-year-old children fell into the overweight category, which could also possibly contribute to the lower prevalence of hypertension that was reported in the study.…”
Section: Discussionmentioning
confidence: 99%
“…BP during childhood is significantly associated with BP during adulthood. 6 Therefore it is important to develop intervention programmes, especially those that are aimed at increasing levels of physical activity that would lead to weight loss in overweight and obese children and thus reduce the risk of hypertension. It is also advised that BP must be monitored from early childhood and that BP readings must be incorporated in the clinical evaluation of children on a routine basis so that possible cardiovascular risk factors can thus be monitored, especially in the case of overweight and obese children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies have assessed the simultaneous secular trends of BMI and BP in children and adolescents [6]. The population-based studies of BP trends, performed in developed and developing countries, have not consistently shown that BP increases in parallel with obesity.…”
mentioning
confidence: 98%